2013
DOI: 10.1371/journal.pone.0077971
|View full text |Cite
|
Sign up to set email alerts
|

The Costs and Cost-Effectiveness of a School-Based Comprehensive Intervention Study on Childhood Obesity in China

Abstract: BackgroundThe dramatic rise of overweight and obesity among Chinese children has greatly affected the social economic development. However, no information on the cost-effectiveness of interventions in China is available. The objective of this study is to evaluate the cost and the cost-effectiveness of a comprehensive intervention program for childhood obesity. We hypothesized the integrated intervention which combined nutrition education and physical activity (PA) is more cost-effective than the same intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 22 publications
1
79
1
1
Order By: Relevance
“…If this cannot be done, China needs to train its own teachers (mainly health teachers) with effective programs. Currently, there are some localized TOT programs reported in our study and in the literature [51,52]. However, few of them have been assessed and generalized to country level.…”
Section: Implications For Research On Delivering Nutrition Educationmentioning
confidence: 95%
“…If this cannot be done, China needs to train its own teachers (mainly health teachers) with effective programs. Currently, there are some localized TOT programs reported in our study and in the literature [51,52]. However, few of them have been assessed and generalized to country level.…”
Section: Implications For Research On Delivering Nutrition Educationmentioning
confidence: 95%
“…57 A study from China showed, in school programmes for children, that physical activity combined with a nutrition programme is more effective than either intervention alone. 58 Through a systematic review of population-wide interventions in adults and children across multiple countries, Laine and colleagues 32 found the most efficient interventions to increase physical activity were community trails built alongside or over abandoned rail tracks ($0·006 per metabolic equivalent of task hours [MET-h]), pedometers ($0·014 per MET-h), and school health education programmes ($0·056 per MET-h). Nearly all physical activity interventions, especially those related to tracking or motivating physical activity, require more detailed evaluation of effectiveness and cost-effectiveness.…”
Section: Cost-effectiveness Of Interventions For Cvrdsmentioning
confidence: 99%
“…Of the 27 included studies, eight studies 34,[37][38][39]43,51,53,54 focused on the community and built environment; seven studies 30,31,33,36,[48][49][50] assessed on nutrition-related policy/education changes, of which five studies 31,33,36,48,50 analyzed state implementations of the U.S. Expanded Food and Nutrition Education Program (EFNEP); nine studies 32,41,42,[44][45][46]52,55,56 focused on school environments; and three studies 35,40,47 evaluated social marketing and media interventions.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Most (15 of 27) studies 32,34,35,[37][38][39][41][42][43]46,51,[53][54][55][56] analyzed policy or environmental changes at the local level, six studies 31,33,36,47,48,50 at the state level, and seven studies 30,40,[44][45][46]49,52 at the national level. Note that the number of studies does not sum to 27 as one study analyzed an intervention at more than one level of government.…”
Section: Evidence Synthesismentioning
confidence: 99%